Basic Concepts, Culture and Organizational Behavior in Developing Good Institutions - Refhani Puspadini (Konsultan Jurnal Ilmiah Indonesia, 2024)
Organizational Behavior is a discipline that studies individual and group-level behavior in an organization and its impact on performance (both individual, group, and organizational performance). Organizational behavior is also known as the study of organizations. As social beings, every human being always interacts with other humans, even tends to live in groups or organizations to achieve common goals that are impossible to achieve if he is alone. The method in this study uses literature studies. The technique used in collecting data in this study is documentation. The stages passed in this technique are searching, collecting, and exploring all information from journals and books that are closely related to the basic concepts, culture and behavior of organizations in developing good institutions. The substance or roots of organizational culture are core characteristics that indicate the traits, properties, elements, or elements inherent in organizational culture. Organizational culture represents a shared perception of members of the organization or in other words, culture is a system of shared meaning. Therefore, the hope that is built from here is that individuals who have different backgrounds or are at different levels in the organization will understand organizational culture with a similar understanding.